Intraparenchymal Schwannoma: A Rare Entity. (2nd November 2021) - Vaphiades, Michael S.; Hackney, James
ABSTRACT: A 60-year-old woman noted headaches, transient visual obscurations and pulsatile tinnitus. She had Frisén grade 4 papilloedema. Brain magnetic resonance imaging showed a large subfrontal cystic mass with ring enhancement. Tumour pathology was in-keeping with an intraparenchymal schwannoma. This uniquely rare tumour is discussed.